Antioxidant Responses, Neurotoxicity, and Metallothionein Gene Expression in Juvenile Korean Rockfish Sebastes schlegelii under Dietary Lead Exposure. Issue 2 (3rd April 2017) - Kim, Jun-Hwan; Oh, Chul Woong; Kang, Ju-Chan
Abstract: This study was conducted to assess toxic effects of dietary lead (Pb) exposure on Korean Rockfish Sebastes schlegelii . Juvenile rockfish were used to evaluate the oxidative stress, neurotoxicity, and metallothionein (MT) gene expression after dietary exposure to lead (as Pb 2+ ; 0, 30, 60, 120 and 240 mg/kg). Superoxide dismutase (SOD) activity, a measure of oxidative stress, was substantially elevated in the livers and gills of fish given dietary Pb greater than 60 mg/kg. Glutathione S-transferase (GST) activity in the liver and gill was significantly increased by dietary Pb > 60 mg/kg. A significant decrease in glutathione (GSH) level was observed in fish liver after exposure to dietary Pb > 30 mg/kg and in the gill after treatment with dietary Pb > 120 mg/kg. Acecyltholinesterase (AChE) was noticeably decreased in the brain by dietary Pb > 120 mg/kg and in the muscle by dietary Pb > 60 mg/kg. Metallothionein gene expression in the liver was stimulated significantly by the Pb exposure. Because dietary Pb exposure had a toxic effect on antioxidant responses, a neurotransmitter, and a specific immune expression in rockfish, the results of this study can be used to determine potential useful markers of Pb toxicity. Received June 11, 2016; accepted March 10, 2017 Published online May 3, 2017